DESIGN AND ANALYSIS OF THE FRAME STRENGTH OF WASTE TRANSPORTING MACHINE USING SOLIDWORKS - Abdul Rahman Agung Ramadhan; Abdul Muchlis; Ibnu Fajar Ridha Ghanni (Asosiasi Dosen Muda Indonesia, 2022)
Garbage is a problem of concern worldwide. Public awareness in disposing of waste that is not in its place causes various kinds of problems, one of the problems that occurs is in rivers or artificial canals. This is what makes many people create tools to make it easier to control improper waste disposal. One of the tools that was created was a garbage collector, in making the design of a garbage collection machine using solidworks software, Galvanized Steel material was used with a rod size of 30 x 30 x 2.6 (mm) as the frame. With a frame size of 1320 mm in length, 790 mm in width and 1133 mm in height. The results of the simulation using solidworks software on the frame of the garbage collection machine are to get the von misses stress value with a maximum stress value (MPa) and a minimum stress value of (MPa), for the displacement value with a maximum stress value of 0.61 mm and for a minimum stress value of 0.00 mm, the safety factor gets a value of 3.55 ul. In the comparison of solidworks and theoretical software values, the value for von misses stress is 0.04%, for displacement is 0.24%, and for safety factor is 0.20%.